Dexrazoxane an allied of nursing in chemotherapy extravasation: Integrative Review - Isabelle Pimentel Gomes; Paula Elaine Diniz Reis; Jean Fabricio de Lima Pereira; Thais Grilo Moreira Xavier (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Nowadays, chemotherapeutics extravasation is considered an oncologic emergency. Anthracyclines are classified as antibiotic chemotherapeutic drugs, and have major power to destroy healthy tissues. With the purpose of identifying evidences related to dexrazoxane, a citoprotective medication used on prevention of tissue lesions caused by anthracycline extravasation, we performed an integrative literature review. It has been selected 24 articles that related dexrazoxane (cardioxane®) has preventive action on extravasation inducted lesions of anthracyclines. Publications about this issue have increased over the last three years. Evidence levels are still low, but already with high recommendation reports.